Efficacy of Bifidobacterium longum, B. infantis and Lactobacillus acidophilus probiotics to prevent gut dysbiosis in preterm infants of 28+0-32+6 weeks of gestation: a randomised, placebo-controlled, double-blind, multicentre trial : the PRIMAL Clinical Study protocol - Marißen, Janina; Hudalla, Hannes; Bork, Peer (BMJ open, 2019)
Introduction: The healthy ‘eubiosis’ microbiome in infancy is regarded as the microbiome derived from term, vaginally delivered, antibiotic free, breastfed infants at 4-6 months. Dysbiosis is regarded as a deviation from a healthy state with reduced microbial diversity and deficient capacity to control drug-resistant organisms. Preterm infants are highly sensitive to early gut dysbiosis. Latter has been associated with sepsis and necrotising enterocolitis, but may also contribute to long-term health problems. Probiotics hold promise to reduce the risk for adverse short-term outcomes but the evidence from clinical trials remains inconclusive and none has directly assessed the effects of probiotics on the microbiome at high resolution.
Gesehen am 31.03.2020